Use of negative pressure wound therapy as a bolster over skin grafts in patients with severe burn injuries at a tertiary care burn centre in India. Issue 3 (July 2021) - Singh, Rajpal; Tripathi, Deepak; Jaiswal, S.P.; Singh, Piyush; Balar, Tasvir; Viradiya, Chirag
Highlights: Negative pressure wound therapy applied as bolster in pilot surgery in patient with deep burn wound who underwent tangential excision followed by autograft/homograft. Decreased pain, hospital stay, and caregiver workload was observed. Decreased healing time, subject's patient to early rehabilitation, further reduces chances of contracture development. Total 13 patients were discharged successfully without need of regrafting. Abstract: Background: Management of deep burn requires aggressive debridement of non-viable burnt tissue and closure with skin grafts or flaps but challenge is to manage wound exudates and patient discomfort and to avoid shear force and pain cause by frequent dressing changes. This observational case series assessed outcomes of negative pressure wound therapy (NPWT) use as a bolster in pilot surgery (primary surgery) over skin grafts in patients with severe burns in a burn center in Indore, India in term of wound healing, pain, caregivers and nurses workload. Methods: Patients with extensive burns (≥30% total body surface area [TBSA]) were admitted to the burn unit between January and December 2020. Acute burn victims (burns present <24 h from burn injury) and patients over the age of 18 were included in this study. All patients received primary standard burn care including debridement of non-viable tissue, wound closure with homograft or autografts, and application of NPWT as a bolster in first sitting (Pilot surgery). NPWT dressings were changed every three to four days. Skin graft healing was monitored during dressing changes. Patient reported pain was recorded using the 10-point Likert pain scale. Results: Thirteen patients with an average TBSA of 42.6% (range 30–63%) underwent treatment. A total of 8 patients suffered from flame burns, 4 from electrical burns, and 1 from scald burns. The average length of hospital stay was 18.1 ± 6.2 days with wound closure in 9.1 ± 4.3 days. An average of 3.5 ± 1.3 dressing changes occurred. All patients were discharged without requiring re-grafting. No complications were observed, except small non-healing burn wounds in four patients that required further standard wound care to reach complete re-epithelisation. The overall patient reported pain was 3.4 ± 1.2. Conclusions: Use of NPWT as a bolster in patients with severe burns resulted in decreased wound healing time, pain score, workload of nursing staff and caregivers and early rehabilitation of survivor.